Anonymous and Verifiable Registration in Databases - Brandt, Jørgen; Damgård, Ivan Bjerre; Landrock, Peter (DAIMI Report Series, 1988)
Methods are given by which personal data about a large number of individuals can be registered in a large central database without having to trust this register not to give away information linked to a given individual. Personal information arriving from many different sources can be placed correctly in the register. The registration is done in a verifiable way: Each individual can be given access to the register to check that his information is correct, and can even, if he chooses to do so, prove to anyone that he is or is not identical to a given person in the register. This can all be done without compromising the anonymity of any other individual.